The Level of Serum Pepsinogen in Diagnosing and Evaluating the Severity of Subacute Combined Degeneration Due to Vitamin B12 Deficiency - Chen, Xiaoyan; Wang, Rong; Huang, Xusheng; Yang, Fei; Yu, Shengyuan (Frontiers in Neurology, 2021)
Subacute combined degeneration (SCD) is a neurological complication of cobalamin deficiency, which is usually caused by chronic autoimmune atrophic gastritis. Serum pepsinogen 1 and the ratio of pepsinogen 1/pepsinogen 2 (PG1/2) can reflect the severity of gastric atrophy. Objective: This work aims to investigate whether decreased serum PG1 and PG1/2 ratio are helpful in diagnosing SCD and reflecting the severity of SCD. Methods: We retrospectively analyzed the clinical and laboratory tests of 65 cases of SCD due to vitamin B12 deficiency and compared the laboratory parameters of SCD with 65 age- and sex-matched amyotrophic lateral sclerosis (ALS) patients. Results: PG1 and PG1/2 ratio were decreased in 80 and 52.3% of SCD patients, respectively. Compared to patients with PG1/2 ratio ≥3.0, patients with PG1/2 ratio <3.0 had more severe anemia, larger mean corpuscular volume (MCV), lower level of vitamin B12, higher folate and homocysteine (Hcy), more severe changes in somatosensory evoked potential (SEP), and higher rate of lesions in spinal MRI (P < 0.05). PG1 and PG1/2 ratio had inverse correlation with MCV and N20 latency in SEP examination (P < 0.05). PG1/2 ratio, RBC count, and Hcy were independent risk factors for SCD in logistic regression analyses. The ROC curve analysis revealed that the diagnostic accuracy of PG1 and PG1/2 ratio was 72.2 and 73.0%, respectively, while the cutoff values were 22.4 ng/ml and 2.43 for SCD, respectively. Conclusions: Decreased PG1 and PG1/2 ratio are helpful for the diagnosis and evaluation of the severity of SCD due to vitamin B12 deficiency.